Consumer profile in terms of food label reading in Mures county, Romania– a pilot study: Consumer profile in terms of food label reading - Avram, Calin; Avram, Laura; Ruta, Florina; Georgescu, Ion Mihai; Rus, Victoria (Progress in Nutrition, 2021)
Introduction. Food labeling is a very important public health tool aiming at providing consumers with information that could influence their purchasing decisions.Aim. Analyzing the frequency of consultation of the food label, the degree of understanding of the information content on the label and the importance of the functional characteristics of the labels in making purchasing decisions in acquaintance with a group of people from Mures County.Material and method. This is a transversal descriptive study, in which we developed an assessment questionnaire on-line . The questionnaire included 27 items.Results. 476 people agreed to participate in this study, the majority of participants being women (79.83%). People with low incomes do not trust the information on the packaging (OR = 1.89, 95% CI: 1.15-3.12) and do not read information from the product labels before purchasing them (OR = 10.39, 95% CI: 2.24-48.11). People with secondary education read the label only when they buy a product for the first time (OR = 0.41, 95% CI: 0.23-0.71) and do not trust the information on the product packaging (OR = 3.02, 95% CI: 1.70-5.38).Conclusions. This study has shown that awareness and use of pre-packaged food labeling information is low among consumers in Mureş County. The results showed that only a quarter of survey respondents had a high awareness of food labeling. The place of work, level of education and age of the respondents have proven to be significantly associated with the awareness and use of pre-packaged food labeling information.